The Most Ancient Bridges in Britain (Proceedings of the Society of Antiquaries of Scotland, 1915)
The article considers early stone bridges from the Roman period, mediaeval wooden bridges, ancient Scottish and Irish bridges, gateways to bridges and the information which can be derived from old illustrations and representations on seals.